Metaphor and its contribution to the study of melancholy as a confrontation of political culture in Ni pan ni circo (2005) - Pequeño Saco, Tamara Paloma (2020)
This paper begins by reflecting, from the perspective of Culture, upon the concept of melancholy, as a consequence of the failure of the left-wing utopia born of the ethics of subaltern sectors. It then goes on to analyze the possibility of examining non-hegemonic literary discourses in order to obtain information about the subjectivity with which their creators perceive context from a memory affected by political defeat. To this end, we analyze the role that metaphor plays in the poems contained in Alejandro Romualdo's book Ni pan ni circo (2005). As a theoretical framework, we employ the proposals contained in Roger Bartra’s Culture and Melancholy (2001), as well as the contributions of Raymond Williams (2000), Robert Burton (2015), Enzo Traverso (2019), and Walter Benjamin (2008).